Safety and Effectiveness of Direct Xa Inhibitors vs Warfarin in Patients with Nephrotic Syndrome - Ayesha Shahjahan, Syed Irfan Ahmed, Aymen Jamal (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Nephrotic syndrome (NS) is characterized by excessive proteinuria (> 3.5 g/day), hypoalbuminemia, and edema. Objectives: The main objective of the study is to find the safety and effectiveness of direct Xa inhibitors vs warfarin in patients with nephrotic syndrome. Material and methods: This cross-sectional study was conducted in Akbar Niazi Teaching Hospital, Barakahu, Islamabad from January 2022 till June 2022. The data were collected from 120 patients which diagnosed with nephrotic syndrome. After permission from hospital ethical committee, total 120 patients meeting the inclusion and exclusion criteria was enrolled in the study. Detailed history of kidney disease and physical examination was done to meet the inclusion and exclusion criteria. Informed consent was obtained. Results: The data was collected from 120 patients. Out of 120 participants, 60 were treated with warfarin while 60 were considered as control group. Median age was 26 years in group I and 25.3 years in group II (p=0.705). Female cases counted for 41 (86%) and 19 (14%) in I and II groups, respectively. Risk factors, clinical presentation, affected vessels and AF for both groups are depicted in Table I. Results from both groups were comparable and statistically, no significant differences were observed (p• value more than 0.05). Practical implication: This study will help in treating nephrotic syndrome and kidney complications. Conclusion: It is concluded that awareness about nephrotic syndrome in patients were low and its prevalence continues to remain high and is likely to increase globally. Direct Xa inhibitors were associated with lower hazards of kidney complications and mortality than warfarin in patients with nephrotic syndrome. Keywords: Nephrotic, Syndrome, Complications, Mortality, Warfarin